Benefits and spillovers of greater competition in Europe: A macroeconomic assessment - Tamim Bayoumi; Douglas Laxton; Paolo Pesenti (Federal Reserve Bank of New York, 2004)
We estimate the macroeconomic benefits and international spillovers of an increase in competition using a general-equilibrium simulation model with nominal rigidities and monopolistic competition in product and labor markets. We draw three conclusions after calibrating the model to the euro area against the rest of the industrial world. First, greater competition produces large effects on macroeconomic performance, as measured by standard indicators. In particular, we show that differences in competition can account for more than half of the current gap in GDP per capita between the euro area and the United States. Second, greater competition may improve macroeconomic management by increasing the responsiveness of wages and prices to market conditions. Third, increased competition can generate positive spillovers to the rest of the world through its impact on the terms of trade.
Keywords: C51; E31; E52; 330; competition; markups; monetary policy; Taylor Rule; Wettbewerb; Monopolistischer Wettbewerb; Allgemeines Gleichgewicht; Theorie; EU-Staaten; Makroökonomischer Einfluss